The Influence of Transformational Leadership and Leader-Member Exchange in Organization on Job Satisfaction and Performance of Employee in Automotive Manufacturing Industry, Eastern Seaboard Industrial Estate, Rayong Province - Kanlaya, Apichaya; Thaweepaiboonwong, Jutamard (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The purposes of this research were to study the level of transformational leadership as a result of employee perceptions, leader-member exchange, employee job satisfaction, and employee performance in the automotive manufacturing industry, Eastern Seaboard Industrial Estate, Rayong Province, and to analyze the influence of transformational leadership, leader-member exchange, and employee job satisfaction on employee performance in the automotive manufacturing industry, Eastern Seaboard Industrial Estate, Rayong Province. The sample consisted of 256 employees from a major auto parts manufacturer in the Eastern Seaboard Industrial Area, Rayong Province. The research used a questionnaire to collect data. The statistics used were frequency, percentage, skewness, kurtosis, mean, standard deviation, correlation coefficient, and structural equation model. From this study, employees perceive their supervisors' transformational leadership and job satisfaction at the highest level (mean=4.58 and 4.72 in sequence). Leader-member exchange and employee performance were at a high level (mean=4.23 and 4.36 in sequence). After adjusting the structural equation model based on the assumptions, it was discovered that CMIN/DF=2.169, GFI=0.931, AGFI=0.893, CFI=0.952, NFI=0.915, RMSEA=0.068, RMR=0.009. Transformational leadership had a positive direct effect on job satisfaction and employee performance with a statistically significant at the .05 level (direct effect values=0.16 and 0.15 in sequence) and leader-member exchange had a statistically significant positive direct effect on employee performance at the .05 level (direct effect value=0.14).